1978
DOI: 10.1126/science.199.4328.555
|View full text |Cite
|
Sign up to set email alerts
|

European Corn Borer: Pheromone Polymorphism or Sibling Species?

Abstract: Electrophoretic analyses of the (Z) and (E) pheromone-attracted males of Ostrinia nubilalis (Hübner), the European corn borer, in an area of coexistence indicate that these strains are not freely interbreeding. Although the populations are morphologically indistinguishable, studies of allozyme, pheromone, and hybridization suggest that the (Z) and (E) entities are genetically differentiated, perhaps to the status of semi- or sibling species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
2
1

Year Published

1990
1990
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(70 citation statements)
references
References 13 publications
1
66
2
1
Order By: Relevance
“…This may lessen stabilizing selection and create opportunities for pheromones to evolve, depending on the suite of selection forces a population is experiencing (21). Interestingly, field populations of the sibling taxon Ostrinia scapulalis (22), which has an identical pheromone polymorphism as O. nubilalis, were found in apparent Hardy-Weinberg equilibrium (23), although such situations have not been reported for O. nubilalis (24).…”
Section: Resultsmentioning
confidence: 95%
“…This may lessen stabilizing selection and create opportunities for pheromones to evolve, depending on the suite of selection forces a population is experiencing (21). Interestingly, field populations of the sibling taxon Ostrinia scapulalis (22), which has an identical pheromone polymorphism as O. nubilalis, were found in apparent Hardy-Weinberg equilibrium (23), although such situations have not been reported for O. nubilalis (24).…”
Section: Resultsmentioning
confidence: 95%
“…Females of the Z-strain produce 97% Z11-14:OAc and 3% E11-14:OAc whereas E-strain females produce 99% E11-14:OAc and 1% Z11-14:OAc (Anglade et al, 1984;Klun and Robinson, 1971;Klun et al, 1973). Consequently, the strains do not freely interbreed in sympatry (Cardé et al, 1978;Malausa et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Pheromone polymorphism became evident when the opposite blend (4: 96 ZIE) was discovered in some New York populations (Kochansky et al 1975). Carde et al (1978) suggested that the two types based on pheromone blend differences might coexist in certain areas but were not freely interbreeding and might actually have evolved to the status of semi-or sibling species. Laboratory hybridization between the two types was obtained (Liebherr & Roelofs 1975), and Klun & Maini (1979) found that hybrid females produce pheromone blends with approximately a 35:65 ZIE ratio.…”
Section: Oac 4% (E)-l1-tetradecenylmentioning
confidence: 99%